The Use of Podcast in Improving Students’ Listening Skill of Senior High School - Saragih, Dhea; Marpaung, Anissa; Saragih, Roselina Purnama Sari (International Journal Corner of Educational Research, 2022)
This research was conducted with the aim of finding the influence of podcast in improving students’ listening skill, especially for senior high school students. The method in this research is qualitative research method, where researchers collected data through questionnaires filled by the students and short interviews with students. The subjects in this research were the students of class XI Mia 1 in SMA Swasta Assisi Siantar. Based on research that the researchers did, researchers found that podcast is a media that has effect on students’ learning processes, especially when studying listening skill. Podcast is one of the learning media that makes students interested and motivated to learn listening in English.